Korelasi Antara Kondisi Keluarga Broken Home dengan Motivasi Belajar Siswa Kelas VIII SMPN 1 Pangkah - Tegar Aji Pamungkas (JCOSE Jurnal Bimbingan dan Konseling, 2021)
Motivation to learn can be obtained from the family. A harmonious family can create good learning motivation. However, in modern times there are many families who are not harmonious. This situation causes students to experience a broken home which results in decreased motivation to learn. This study aims to prove the relationship between broken home families and student motivation. This research is a quantitative study using the ex post facto method. The population in this study were all students of class VIII SMPN 1 Pangkah with a research sample of class 8A, 8D, and 8I totaling 95 students. Data collection was carried out by using observation techniques, filling out questionnaires, and psychological scales. The data collected were then analyzed by simple linear regression test after previously having carried out the normality test, linearity test, and hekteroscedasticity test. After collecting the data, it was concluded that from 95 respondents, 80 respondents had a bad family category and 5 respondents were in very bad category. After the regression analysis was carried out, it was found that there was a relationship between broken home families and student learning motivation as much as 22.7%, so it could be concluded that there was a proven relationship between the condition of the broken home family and the learning motivation of the eighth grade students of SMPN 1 Pangkah.